Ageing, demographic risks, and pension reform - Jukka Lassila; Tarmo Valkonen (The Research Institute of the Finnish Economy (ETLA), 2001)
Ageing will increase pension expenditure and contribution rates. There is also increasing awareness that the risks connected to mortality, fertility, and migration are considerable. In pension reforms one must decide how these risks are to be shared between workers and pensioners, and also take into account that in the transition phases different cohorts may gain or lose. We discuss the risk-sharing and intergenerational distribution aspects of three pension policy measures that either have already been adopted or are being proposed in Sweden and Finland. Each of these methods, linking benefits to life expectancy, indexing benefits to the total wage bill, and using fertility-dependent prefunding, has its own advantages and weaknesses. Using a numerical OLG model, and realisations from stochastic population simulations, we demonstrate that these methods greatly enhance the sustainability of a pension system in unfavourable demographic outcomes but have practically no effects if the demographics remain stable. Thus the allocation of risks can be improved without fundamentally changing the systems. – – Tavoitteena on tutkia, miten eläkepoliittisilla toimilla voidaan tasata väestön ikääntymisen aiheuttamaa eläkemaksujen nousupainetta. Lähtökohtana on, että väestön ikääntymisen määrää ei etukäteen tiedetä: syntyvyyteen, kuolevuuteen ja siirtolaisuuteen liittyy kaikkiin merkittävää epävarmuutta. Tarkasteltavia toimenpiteitä ovat työeläkkeiden indeksointi, elinajanodotteen nousun huomioiminen eläkkeissä, ja rahastoinnin sitominen syntyvyyteen. Arviointikriteereinä käytetään vaikutuksia kansantaloudellisiin muuttujiin, työnantajan ja työntekijän eläkemaksuihin, eläkejärjestelmän oikeudenmukaisuuteen ja kotitalouksien hyvinvointiin. Jos väestökehitys on vakaata, ei toimenpiteillä ole juurikaan vaikutuksia. Jos taas väestökehitys osoittautuu epäsuotuisaksi, nämä toimenpiteet tasaavat väestön ikääntymisen kustannuksia tehokkaasti eri sukupolvien kesken. Täten ne parantavat väestöriskien kohdentumista eri sukupolville. Tuloksia on laajemmin esitelty julkaisussa Työeläkkeiden indeksointi, elinaikakorjaus ja väestön ikääntyminen, Eläketurvakeskuksen tutkimuksia 2000:2 ja ETLA B 172. – työeläkkeet ; väestöepävarmuus ; elinajanodote ; indeksointi ; rahastointi
Keywords: H55; J11; 330; Demographic uncertainty; pension benefits; longevity adjustment; indexing; partial prefunding; voting; Bevölkerungsentwicklung; Rentenreform; Lohnniveau; Simulation; Finnland; Alternde Bevölkerung